Plans for the Elimination of Architectural Barriers: Experiences in Tuscany - Marzi, Luca (TeMA - Journal of Land Use, Mobility and Environment, 2009)
Plans for removal architectural barriers are meta-planning instruments, necessary to start coordinated procedures of “urban design”, in order to realize all the interventions that can minimise conflicts between man and environment. We must start from all those people that need more these kind of attentions, to be able to define all the answers that can guarantee the usability and accessibility of a town more sensitive to disability.